The hookup plan - Rochon, Farrah (Rochon, Farrah. Boyfriend project, 2022)
"London Kelly has worked incredibly hard to become a successful pediatrician, but the stress of her job never eases. Ready to let loose a little bit, she figures a one-night stand at her high school reunion with the incredibly sexy Drew Sullivan will be the perfect way to forget about her work troubles. But she soon finds out that Drew has been hired by the hospital where she works to spearhead a buy-out. Now London and Drew are on opposite sides of the boardroom table, while she tries to protect her patients and her job. Good thing she has her two besties, Samiah and Taylor, to help her sort everything out"--